Chloride corrosion resistance of underwater repair concrete in terms of the cutting effects of hydrostatic pressure - Elżbieta Horszczaruk; Piotr Brzozowski; Teresa Rucińska (Budownictwo i Architektura, 2013)
The paper presents the results of the study of underwater repair concrete under the effect of the salt mist. The research was conducted in accordance with the standard PN-EN 14147. Concrete samples for testing the corrosive elements of that test were taken during the first 7 days of insight in the pressure vessel and were subjected to hydrostatic pressure effects from 0,1 to 0,5 MPa. The beneficial effect of hydrostatic pressure on the corrosion resistance of tested concrete repair was. Was observed samples taken from the surface layers of the tested elements showed slightly higher resistance to chlorides which confirmed the characteristics of pore distribution of concrete in the studies.